The Attention Training Technique Reduces Anxiety and Depression in Patients With Coronary Heart Disease: A Pilot Feasibility Study - Dammen, Toril; Tunheim, Kristoffer; Munkhaugen, John; Papageorgiou, Costas (Frontiers in Psychology, 2022)
Background and objectives: Depression and anxiety symptoms are highly prevalent in coronary heart disease (CHD) patients and associated with poor outcome. Most psychological treatments have shown limited effectiveness on anxiety and depression in these patients. This study evaluates the feasibility of the attention training technique (ATT) in CHD patients with symptoms of anxiety and/or depression. Methods: Five consecutive CHD patients with significant depression and anxiety symptoms with Hospital Anxiety and Depression rating scale (HADS) -anxiety or -depression subscale score > 8 received six weekly group-sessions of ATT in an open trial. Outcomes included feasibility and symptoms measured by HADS, at baseline, post-treatment and at six months follow-up. We also assessed psychiatric diagnoses, type D personality, insomnia, worry and rumination. Results: The sample comprised five men with a mean age of 59.9 (SD 4.4) years. Four of the patients attended all six sessions, and one patient attended all but one session. Mean HADS-A scores at baseline, post-treatment, and follow-up were 9.4 (SD 3.0), 4.2 (SD 3.0) and 4.0 (SD 2.5), and for HADS-D 8.6 (SD 3.3), 3.0 (3.7) and 1.6 (SD 1.5), respectively. The results showed clinically significant changes in anxiety, depression, psychiatric disorders, insomnia, worry, and rumination. Statistically significant changes were found from pre- to post treatment for HADS-A and worry, which was maintained at follow-up, and HADS-D significantly decreased from pre-treatment to 6-months follow-up. Conclusions: ATT in a group format appears to be a feasible stand-alone metacognitive treatment for CHD patients. An adequately powered randomised controlled trial is warranted.